Sustainable maritime transportation and exploitation of sea resources [electronic resource] - International Maritime Association of the Mediterranean. International Congress 550101; Rizzuto, E. 549730; Soares, C. Guedes 254426 (Boca Raton, Fla. : CRC Press, 2012)
Includes bibliographical references and indexes